IMPROVEMENT OF MRO MATERIAL PROCUREMENT EFFICIENCY THROUGH THE SIX SIGMA CONCEPT AT PT KRAKATAU STEEL (PERSERO) TBK - Wijanarko, Wahyu
PT Krakatau Steel (Persero) Tbk (PTKS) is a State-Owned Enterprise engaged in the production of Steel and related services. PTKS's Production Capacity reaches 4 million Tons per year until the end of 2022. Its leading products include Hot Rolled Steel, Cold Rolled Steel and Wire Rod Steel. To maintain the Company's competitiveness, PTKS must operate efficiently and ensure the availability of products in the market to meet customer needs at competitive prices. One of the factors related to the smoothness and efficiency of production is the availability of Material Maintenance, Repair & Operation (MRO). The MRO Procurement Department is a unit that functions to process MRO Material procurement at PTKS. The problem currently faced is that the Lead Time for the MRO material procurement process takes a long time, the cause is that the procurement process is not fully digital so that the usage time is not optimal, besides that spot and repeated procurement is often carried out for the same material. Seeing the situation above, this study applies the Six Sigma method with DMAIC tools consisting of Define, Measure, Analyze, Improve and Control. By using this approach, it is hoped that it can provide business solutions for PTKS. The results of the study show that the lead time for MRO material procurement at PTKS is significantly delayed and inefficient. The analysis shows that this problem is caused by several factors, including less than optimal coordination between departments, less than optimal procurement process management, and lack of integration and automation of information systems. These problems cause serious operational and financial challenges for PTKS, such as decreased operational performance and increased costs. Through the application of the Six Sigma concept, this study analyzes that increasing the efficiency of MRO procurement can be the right solution to overcome these problems. The Define, Measure, Analyze, Improve, and Control (DMAIC) phase is used in this study to identify the root of the problem and develop strategies that can improve the efficiency of the procurement process. The results of this analysis lead to the use of Blanket Purchase Agreement (BPA) contracts and the implementation of E-Procurement as solutions to reduce lead time and improve the efficiency of MRO material procurement at PTKS.